Non-thermal Plasma Treatment of ESKAPE Pathogens: A Review - Scholtz, Vladimír; Vaňková, Eva; Kašparová, Petra; Premanath, Ramya; Karunasagar, Iddya; Julák, Jaroslav (Frontiers in Microbiology, 2021)
The acronym ESKAPE refers to a group of bacteria consisting of Enterococcus faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomonas aeruginosa, and Enterobacter spp. They are important in human medicine as pathogens that show increasing resistance to commonly used antibiotics; thus, the search for new effective bactericidal agents is still topical. One of the possible alternatives is the use of non-thermal plasma (NTP), a partially ionized gas with the energy stored particularly in the free electrons, which has antimicrobial and anti-biofilm effects. Its mechanism of action includes the formation of pores in the bacterial membranes; therefore, resistance toward it is not developed. This paper focuses on the current overview of literature describing the use of NTP as a new promising tool against ESKAPE bacteria, both in planktonic and biofilm forms. Thus, it points to the fact that NTP treatment can be used for the decontamination of different types of liquids, medical materials, and devices or even surfaces used in various industries. In summary, the use of diverse experimental setups leads to very different efficiencies in inactivation. However, Gram-positive bacteria appear less susceptible compared to Gram-negative ones, in general.